Evaluating effective interventions for dyslexic children: Insights and future directions from a systematic literature review - Hayati, Rahma; Iswara, Prana Dwija; Muqodas, Idat; Yuliani, Adit (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
Dyslexia is a disorder in the left brain's nervous system, which is crucial for identifying strephosymbolia to process meaning that will be used for reading, writing, and communication. Although dyslexia is a disorder that hinders normal learning processes, various interventions can be done to address the disorder. The purpose of this research is to provide a comprehensive understanding to researchers, prospective researchers, parents, and experts about the methods, measures, subjects, and approaches used by previous researchers related to interventions that can be given to dyslexic children. The focus of this research is on significant improvement and intelligent adaptation for future research design. This article adopts a qualitative approach with the Systematic Literature Review (SLR) research method. A literature review serves as the initial foundation to assist further research in the future to find information related to the topic to be studied and to avoid errors and benefit from their experience. The database used in the literature search is Harzing's Publish or Perish with online database sources from Google Scholar and Scopus. The search was done using several keywords in Indonesian and English separately, including 1)